2017
DOI: 10.1039/c7tb01510k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanoparticles coated with hyaluronic acid lipoid for targeted co-delivery of paclitaxel and curcumin to synergistically eliminate breast cancer stem cells

Abstract: HA-modified hybrid nanoparticles for targeted co-delivery of paclitaxel and curcumin to synergistically eliminate breast cancer stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 42 publications
0
63
0
Order By: Relevance
“…As found with other tridimensional in vitro models and other PSs [14,32], TPCS 2a localized mainly in the more external cells layers of the mammospheres, and penetrated deeper at increasing incubation time. Weak penetration into the core of MCF-7 mammospheres was observed also with coumarin-loaded HA hybrid NPs [33].…”
Section: Discussionmentioning
confidence: 86%
“…As found with other tridimensional in vitro models and other PSs [14,32], TPCS 2a localized mainly in the more external cells layers of the mammospheres, and penetrated deeper at increasing incubation time. Weak penetration into the core of MCF-7 mammospheres was observed also with coumarin-loaded HA hybrid NPs [33].…”
Section: Discussionmentioning
confidence: 86%
“…44,45 Curcumin also has many functions such as antibacterial, anti-inflammatory, analgesic and wound healing properties, and its immunomodulatory potential in many inflammatory disease models has been demonstrated. 46,47 Moreover, studies have shown that curcumin protects against myocardial fibrosis through various mechanisms. For example, curcumin inhibits myocardial fibrosis by inhibiting the activation of MMP-9, TIMP-1 and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the HA‐PLGA NPs delivered drugs to breast cancer in vitro and in vivo and reduced number and migration of breast cancer stem cells (bCSCs) by targeting their surface marker CD44. More importantly, HA‐hybrid co‐delivered NPs showed significant tumor growth inhibition by synergistically inhibiting the proliferation of non‐bCSCs and bCSCs in MCF7 xenografted tumor models . Wang et al.…”
Section: Nanocarriersmentioning
confidence: 99%